Dynamics and geo-ecological characterization of vegetable communities from Ellemberg’s indicator values and the method Phytoindication/Phytoaction. A trial application in the tamarisks of the Aceitero creek (Guadaíra basin, Seville) - Gómez Montblanch, David Cristel; Laguna Lumbreras, Emilio; Meaza Rodríguez, Guillermo (Geographicalia, 2014)
The geo-ecological characterisation of a riparian gallery community dominated by French Tamarisk (Tamarix gallica) in Aceitero creek (province of Seville, Spain) has been made by two approaches: 1) the use of Ellemberg’s indicator values, combinated with cover averages, as proposed by Laguna (2012), and 2) the method Fi/Fa (Interactivity Phytoindication/Phytoaction) proposed by Meaza & Cuesta (2010). But previously, we have carried out an analysis of structure and dynamics through the combinated use of statistics and the proposal of sociological classification of trees in forests (Harold, 1984). Both approaches yield that the sampled Tamarisk gallery thicket is a plant community which combinates hygrophile and nitrophile species, so being mostly dominated by hygro-nitrophile species. We conclude that both methodological approaches can be used in a complementary way.
Keywords: Tamarix; ellenberg indicator values; phytoindication/phytoaction; Seville; Spain